2020
DOI: 10.1021/acsnano.0c04801
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bandgap-like Strong Photoluminescence from Twisted Multilayer MoS2 Grown on SrTiO3

Abstract: While direct bandgap monolayer 2D transition metal dichalcogenides (TMDs) have emerged as an important optoelectronic material due to strong light−matter interactions, their multilayer counterparts exhibit an indirect bandgap resulting in poor photon emission quantum yield. We report strong direct bandgap-like photoluminescence at ∼1.9 eV from multilayer MoS 2 grown on SrTiO 3 , whose intensity is significantly higher than that observed in multilayer MoS 2 / SiO 2 . Using high-resolution electron microscopy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
(60 reference statements)
2
20
0
Order By: Relevance
“…Since the Raman interval reflects the microcosmic interlayer distance, the smaller Raman interval clearly implies a larger interlayer distance and weaker interlayer coupling strength in anomalous bilayers. According to previous reports [ 30 , 31 ], weaker interlayer coupling strength can help increase PL yield of bilayer and many-layer MoS 2 owing to the modification of band structure. As interlayer distance increasing and the indirect transition being suppressed, bilayer and many-layer can also exhibit direct-bandgap-like emission, which is quite similar to our anomalous bilayers with giant PL intensity enhancement.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Since the Raman interval reflects the microcosmic interlayer distance, the smaller Raman interval clearly implies a larger interlayer distance and weaker interlayer coupling strength in anomalous bilayers. According to previous reports [ 30 , 31 ], weaker interlayer coupling strength can help increase PL yield of bilayer and many-layer MoS 2 owing to the modification of band structure. As interlayer distance increasing and the indirect transition being suppressed, bilayer and many-layer can also exhibit direct-bandgap-like emission, which is quite similar to our anomalous bilayers with giant PL intensity enhancement.…”
Section: Resultsmentioning
confidence: 84%
“…While monolayer TMDCs, such as molybdenum disulfide (MoS 2 ), are direct bandgap materials with evident emission in the visible range, bilayer and few-layer TMDCs turn to be indirect-bandgap semiconductors with much suppressed photoluminescence (PL) yield [ 10 , 25 , 26 , 27 , 28 , 29 ]. As a result, fundamental researches of physics and explorations of functional devices based on TMDCs mainly focus on their monolayer counterparts [ 10 ], where optical densities are limited with atomic monolayer thickness [ 30 , 31 ]. In order to utilize the optical densities with increasing layer thicknesses, various approaches have been developed to enhance the PL yield of bilayer and few-layer TMDCs such as applying strain [ 32 , 33 , 34 ] or lateral electric fields [ 35 ], modifying growth conditions [ 30 ], and intercalation of light atomic species in the interlayer gap [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] A previous study has concluded that the proportion of phonon-free direct bandgap transition of TMDs will increase with increasing interlayer distance, since it gives rise to reduced deviation of the direct band and indirect band. [45] Therefore, increasing the dielectric constant of the substrate of 2DMs can give rise to enhanced light-matter couplings as more highefficiency phonon-free transition paths are becoming available (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent studies have witnessed the effective modulation of the properties of the MoS 2 films rendered from the different supports. [21][22][23][24][25][26][27][28][29][30][31][32] On the one hand, distinct substrate materials can induce different charge separation at the interfaces and establish varied dipole fields at the corresponding heterojunctions, which strictly depends on the actual components as well as the atomic structures of the interfaces. [33,34] On the other hand, additional tuning effects can be obtained via nanostructuring the substrate surface, which has provided a more-open strategy for tuning the transportation and luminescence properties of MoS 2 .…”
mentioning
confidence: 99%